Concentrations of migrated mineral oil/polyolefin oligomeric saturated hydrocarbons (MOSH/POSH) in Chinese commercial milk powder products. Issue 8 (3rd August 2019) - Zhang, Shuchang; Liu, Lingling; Li, Bingning; Xie, Yaoqing; Ouyang, Jie; Wu, Yanwen
ABSTRACT: Mineral oil contaminants migrated from food contact materials have raised much concern in the past few decades. However, survey data of the occurrence of mineral oils in foods are only available for a limited variety of foods, which do not include the contaminants in Chinese milk powders. Thus, to conduct an analysis of mineral oils migrated into milk powder products from different packaging materials, 50 Chinese commercial samples (including 38 infant formulas), which were packaged in metal cans, paper containers, paper boxes and aluminium foil-plastic bags, were analysed. Mineral oil saturated hydrocarbons (MOSH), polyolefin oligomeric saturated hydrocarbons (POSH) and aromatic hydrocarbons (MOAH) migrated into those samples were extracted and quantitatively analysed by on-line liquid chromatography coupled with gas chromatography (LC-GC). The results indicated no surface MOAH was detected in any of the samples, while 33 samples contained MOSH/POSH with surface contents of 0.10 ~ 5.09 mg kg −1 . Moreover, the amounts of those MOSH/POSH are closely related to packaging materials, among which the surface contamination values of products in metal cans were the lowest, followed by products in paper containers and boxes, and the values of samples in aluminium foil-plastic bags were the highest. In addition, the surface MOSH/POSH content exhibited a positive correlation with fat content in the samples due to their similar polarities. Graphical abstract: